Sustainability of cacao farms in the district of Huicungo (San Martín, Perú) with the “rapid agroecological method” - Tuesta, O. (2017)
This work was carried out with the objective to determine the sustainability of cocoa farms in the district of Huicungo (San Martín, Perú) by using the “Rapid Agroecological Method”. The study was conducted in the San Martín region, province of Mariscal Cáceres, district of Huicungo. The zone has an annual precipitation of 1, 200 mm and an annual temperature of 30ºC. For the sustainability analysis, we selected “type farms” from each of the three groups found in the area. In each of these, indicators of soil quality and crop health were evaluated using values ranging from 1 to 10 (1: less sustainable, 10: more sustainable). With the collected data, Duncan Test (p ≤ 0.05) was performed to determine the statistical differences between the “type farms”. Results showed the evaluated cacao farms had values greater than five, therefore, they are sustainable. There were no statistical differences between the three “type farms” studied here.